„Daher kommt es, dass in Basel jedermann französisch spricht“. Jugendliche Basler_innen im Welschland (18. und frühes 19. Jahrhundert) - Elise Voerkel (Genre & Histoire)
From the 17th until the 19th century, it was common in German-speaking Switzerland to send children between the ages of 11 and 15 years to the French-speaking parts of Switzerland for language training. This practice was not reserved to the rich nor was it for boys only. According to the parents’ means and preferences, children were sent to private host families, either against money or on the basis of an exchange with another child, or they were sent to professional institutes. There are different motivations for these stays in so-called “Welschland”: apprenticeship in trade, education in general, health, autonomy, and maturity. Letters exchanged between parents and their offspring show that parents remained engaged in the education of their children, despite the distance. In this paper, general aspects of these journeys are described, using statements of the time and in particular funeral orations from Basel (1760-1840). Subsequently, the question of female education in private boarding schools is analyzed by using families’ correspondence.